The Study of Ma'anil Hadith: A Contextual Analysis of The Meaning of Hadith on Women's Leadership - Imam Ahmadi (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This study examines the contradictions of the Hadith prohibiting women as leaders contextually which had become a hot debate among the ulama madhhab. Rooted in historical cultural roots, women are seen as inferior in their position under men's dignity. Women are believed to be a disgrace to the family because they are physically weak on the battlefield and are enslaved as biological satisfactions for their husbands. Although women in the era of jahiliyyah society have eroded their rights, now in the era of Muslim society women are recognized for their rights and are held in high esteem as mothers. Some evidence of gender equality in Islam is in the arguments stated by the Prophet Muhammad in the hadith and the word of God in the Qur'an. This discourse was studied using the library research method with a literature study approach model. The purpose of this study is to explain the relationship between matan hadith and culture and to give meaning to the hadith of women's leadership from a cultural perspective. The scope revolves around the hadith of women's leadership with the boundaries of the present and past cultural customs of society. This study resulted: (a) Traditionally, women play a more important role in protecting the family, both husband and children, (b) The hadith prohibiting women's leadership has an asbab al-wurud side which is not sufficiently understood in text because in context women still have the right of authority as leaders.